Proteomic Mapping of Multifunctional Complexes Within Triatomine Saliva - Santiago, Paula Beatriz; Charneau, Sébastien; Mandacaru, Samuel Coelho; Bentes, Kaio Luís da Silva; Bastos, Izabela Marques Dourado; de Sousa, Marcelo Valle; Ricart, Carlos André O.; de Araújo, Carla Nunes; Santana, Jaime Martins (Frontiers in Cellular and Infection Microbiology, 2020)
Triatomines are hematophagous insects that transmit Trypanosoma cruzi, the etiological agent of Chagas disease. This neglected tropical disease represents a global health issue as it is spreading worldwide. The saliva of Triatominae contains miscellaneous proteins crucial for blood feeding acquisition, counteracting host's hemostasis while performing vasodilatory, anti-platelet and anti-coagulant activities, besides modulating inflammation and immune responses. Since a set of biological processes are mediated by protein complexes, here, the sialocomplexomes (salivary protein complexes) of five species of Triatominae were studied to explore the protein-protein interaction networks. Salivary multiprotein complexes from Triatoma infestans, Triatoma dimidiata, Dipetalogaster maxima, Rhodnius prolixus, and Rhodnius neglectus were investigated by Blue-Native- polyacrylamide gel electrophoresis coupled with liquid chromatography tandem mass spectrometry. More than 70 protein groups, uncovering the landscape of the Triatominae salivary interactome, were revealed. Triabin, actin, thioredoxin peroxidase and an uncharacterized protein were identified in sialocomplexes of the five species, while hexamerin, heat shock protein and histone were identified in sialocomplexes of four species. Salivary proteins related to triatomine immunity as well as those required during blood feeding process such as apyrases, antigen 5, procalins, and nitrophorins compose different complexes. Furthermore, unique proteins for each triatomine species were revealed. This study represents the first Triatominae sialocomplexome reference to date and shows that the approach used is a reliable tool for the analysis of Triatominae salivary proteins assembled into complexes.